IMPORTANT ROLE OF TRANSLATION STUDIES - Sheraliyeva, Shaxnoza (Журнал иностранных языков и лингвистики, 2023)
Our article focuses on observing the development of translation studies through three concepts of translation studies; product-based, process-based, and function-based translation studies. Students are introduced to some well-known translation scholars, including their views on translation scholars. In subsequent discussions, this study enables students to identify the main problems of translation studies, with a focus on discussions of equivalence and variation in the analysis of intertextual texts. To show the extent to which changes occur in the research process, some tendencies to change such as different grammar and sentence structures, diglossia leaks, and pragmatic considerations are mentioned. Based on these trends, therefore, this study ends with a description of Matthiessen’s ideas that have been proposed to develop a parameter to measure changes in meaning. This study can help those interested in translation research, and theories can help provide options useful for their analysis.